Effect of fluid dynamic conditions on 2, 3‐butanediol production by Raoultella terrigena in SBTR: oxygen transfer and uptake rates. Issue 6 (1st November 2016) - Rodriguez, Alberto; Ripoll, Vanessa; Santos, Victoria E; Gomez, Emilio; Garcia‐Ochoa, Felix
Abstract: BACKGROUND: The fluid dynamic conditions play a key role in the development and scaling‐up of bioprocesses. In aerobic cultures, oxygen is an essential substrate for microbial growth, production and culture maintenance; an effective gas–liquid transfer must be achieved. Changes in fluid dynamics due to stirrer speed can affect the culture negatively, causing hydrodynamic stress (increasing shear stress) or oxidative stress (by an increase of available oxygen in the liquid phase). RESULTS: Under oxygen‐limiting conditions, specific growth rate increases with stirrer speed, and several fermentation products were specifically released to the culture medium. 2, 3‐butanediol production increased with stirrer speed, reaching a maximum at 400 rpm. When the agitation was increased over 550 rpm, the metabolic flux was mainly routed to increase the cell growth. Negative effects of fluid dynamic conditions on biomass production were observed at 1900 and 2000 rpm. Cellular response to shear stress conditions was also shown in the large increase of the broth viscosity over time. CONCLUSIONS: Raoultella terrigena is able to adapt the carbon metabolic flux to the availability of oxygen, producing fermentation products, alcohols or directing microbial growth. Moreover, cells can withstand aggressive agitation conditions (up to 1600 rpm). © 2016 Society of Chemical Industry